2012
DOI: 10.1016/j.wocn.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

How linguistic and probabilistic properties of a word affect the realization of its final /t/: Studies at the phonemic and sub-phonemic level

Abstract: This paper investigates the realization of word-final /t/ in conversational standard Dutch. First, based on a large number of word tokens (6747) annotated with broad phonetic transcription by an automatic transcription tool, we show that morphological properties of the words and their position in the utterance's syntactic structure play a role for the presence versus absence of their final /t/. We also replicate earlier findings on the role of predictability (word frequency and bigram frequency with the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 32 publications
(52 reference statements)
4
34
2
Order By: Relevance
“…As noted above, this finding contrasts with some previous CSD studies (Walker, 2012), but is unsurprising if CSD is viewed as a case of segmental reduction, given that word frequency (or predictability) is often positively correlated with reduction probability in such processes cross-linguistically (e.g., Bell et al, 2009;Ernestus et al, 2006;Jurafsky et al, 2001;Schuppler et al, 2012;Zipf, 1929). What is important for our purposes is not the existence of an overall frequency effect, but the fact that it significantly modulates the effect of following context: The higher the frequency of the t/d-final word, the less its deletion rate depends on the identity of the following segment.…”
Section: Word Frequency and Speech Ratecontrasting
confidence: 63%
See 1 more Smart Citation
“…As noted above, this finding contrasts with some previous CSD studies (Walker, 2012), but is unsurprising if CSD is viewed as a case of segmental reduction, given that word frequency (or predictability) is often positively correlated with reduction probability in such processes cross-linguistically (e.g., Bell et al, 2009;Ernestus et al, 2006;Jurafsky et al, 2001;Schuppler et al, 2012;Zipf, 1929). What is important for our purposes is not the existence of an overall frequency effect, but the fact that it significantly modulates the effect of following context: The higher the frequency of the t/d-final word, the less its deletion rate depends on the identity of the following segment.…”
Section: Word Frequency and Speech Ratecontrasting
confidence: 63%
“…16 These methodological changes may help to clarify the interplay between segmental and prosodic factors in conditioning deletion rate, in line with Kendall's (2013) suggestion that variable processes can be better understood by a more detailed consideration of the role of prosodic information (pauses and speech rate). The suggested methodological change applies more generally to sociolinguistic, phonetic, and phonological studies of any variable process that can take place across word boundaries, such as final [t]-deletion in German and Dutch (closely related to English CSD) or Spanish /s/-lenition; in these literatures, 'pause' (as a proxy for boundary strength) is often treated as a possible following context (e.g., File-Muriel & Brown, 2011;Schuppler et al, 2012).…”
Section: Boundary Strengthmentioning
confidence: 99%
“…Further, we found that the higher the probability of the following word, the more often obstruents and liquids were absent. This observation is in line with the results of, for instance, Schuppler, Van Dommelen, Koreman, and Ernestus (2012), who reported that constrictions, bursts and alveolar friction in Dutch /t/ are more likely to be absent in word combinations of higher frequencies.…”
Section: Categorical Versus Gradient Reduction Processessupporting
confidence: 93%
“…Such an analysis involves a fairly powerful view of the language-specific phonetic component, while reducing the role of phonology, but it does not include direct interactions between phonetics and morphology or the lexicon. Whether or not such interactions occur is an empirical question, but not one that has been settled (Cho, 2001;Hanique & Ernestus, 2012;Hay, 2004;Lammert et al, 2014;Mousikou et al, 2015;Schuppler et al, 2012;Song et al, 2013;Sugahara and Turk, 2009). Thus, decisions on how to model the effects of word boundaries on gestural coordination must await further developments in this area.…”
Section: The Relevance Of Syllable Structurementioning
confidence: 99%